Alocação de recursos de rádio em redes de comunicação com alimentação sem fio e multiplo acesso não-ortogonal - Carvalho, Jair Alves de (2020)
ABSTRACT In this work, we investigate radio resource allocation in a wireless powered communication network (WPCN) with non-orthogonal multiple access (NOMA). Specifically, we analyze the resource management of the network through two different optimization problems. The first problem studies the maximization of the sum rate in a WPCN with NOMA that satisfy minimum data rate requirements per user. Moreover, we derive closed-form solutions for the time-splitting ratio and power allocation coefficients that maximize the approximated sum rate NOMA expression. The optimal solution of the sum rate maximization problem is found through Newton’s method with fast convergence. The second problem investigates user fairness in the same network with the aim of maximizing the equal individual data rates. Additionally, it is proposed the bisection method to obtain the optimal power allocation coefficients, and Newton’s method combined with the sub-gradient method to obtain the optimal time-splitting ratio. Lastly, suboptimal solutions of low computational cost are presented for both problems, and simulation results are provided to evaluate the performance of the proposed solutions.